Modelo Estratégico para la Extensión y Proyección Social de la Facultad de Ingeniería de Sistemas e Informática de la Unsm -T - Domínguez Yap, Miguel Ángel (2015)
The present research, entitled Strategic Model for Extension and Social Projection of the Faculty of Engineering and Computer Systems UNSM-T; general objective, design a model to develop a projection and extension in the Faculty of Engineering and Information Systems FISI, also diagnose specific objectives of the current situation involving the process managers, teachers, workers and students as well as extension activities observed in the FISI, university. For developing different methodologies are used. For the collection of information, surveys, interviews, as well as university extension models, design innovation based on a communicative perspective model they were made favoring the protagonist action of different stakeholders in the process of extension. Seen the need to improve the process of interpretation of soil analysis in the laboratory of soils UNSM-T and taking aim at improving the performances mentioned above and support to the laboratory if they provide to beneficiaries in the region San Martin ( students, postgraduate students agrochemical companies and farmers will have an easier interpretation and therefore a good fertilizing his field resulting in a significant improvement in the level of production in tons per year; this thesis aims to support and optimize through Information system of knowledge the process of interpreting a soil testing lab UNSMT. As a result, the scope of the investigation is to manage extension and outreach at the School of Systems Engineering and Computer UNSM-T To research the following hypothesis was formulated:. If a strategic model for managing extension and outreach at the Faculty of Engineering and Computer systems UNSM-T is applied, based on a communicative perspective that enables the active participation of the stakeholders involved, then positive results achieved in the communities in the area of influence of the UNSM-T